Ответы и объяснения

2013-02-06T22:25:38+04:00

7 7/30 - (5 11/30 - Y ) =3 19/30

7 7/30- 3 19/30=5 11/30 - Y

5 11/30 - Y= 3 18/30

Y=5 11/30-3 18/30

Y=1 23/30

 

 

 (X - 1 9/17) + 2 14/17=5 5 /17

X - 1 9/17=5 5 /17- 2 14/17

X - 1 9/17=2 8/17

X=2 8/17+1 9/17

X=3 17/17

X=4

2013-02-06T22:30:11+04:00

7 7/30 - (5 11/30 - Y ) =3 19/30 раскрываем скобки

7 7/30 -5 11/30 +у=3 19/ 30 приводим дроби к одному знаменателю 30 и переводим дроби в неправильные

217/30 - 161/30+у =109/30

у=109/30-217/30+161/30

у=53/30=1 23/30

 

(X - 1 9/17) + 2 14/17=5 5 /17 (скорее всего 5 5/17?)

х- 1 9/17 + 2 14/17 = 5 5/17

х-26/17+48/17=90/17

х=90/17+26/17-48/17

х=68/17=4